2017
DOI: 10.3748/wjg.v23.i42.7635
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of healthcare-seeking behavior among Chinese patients with irritable bowel syndrome

Abstract: AIMTo analyze predictors of healthcare-seeking behavior among Chinese patients with irritable bowel syndrome (IBS) and their satisfaction with medical care.METHODSParticipating patients met IBS Rome III criteria (excluding those with organic diseases) and were enrolled in an IBS database in a tertiary university hospital. Participants completed IBS questionnaires in face-to-face interviews. The questionnaires covered intestinal and extra-intestinal symptoms, medical consultations, colonoscopy, medications, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The information of studies related to depressive symptoms has been summarised in Table S3. Analysis of 47 articles indicated that the pooled prevalence of depressive symptoms was 28.8% (95% CI: 23.6‐34; I 2 = 99.1%) in 22 842 IBS patients (Figure ). Visual inspection of the funnel plot indicates some asymmetry (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…The information of studies related to depressive symptoms has been summarised in Table S3. Analysis of 47 articles indicated that the pooled prevalence of depressive symptoms was 28.8% (95% CI: 23.6‐34; I 2 = 99.1%) in 22 842 IBS patients (Figure ). Visual inspection of the funnel plot indicates some asymmetry (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with organic GI diseases, connective tissue diseases, and metabolic diseases as confirmed by laboratory and endoscopy examinations in the last year were excluded. 15 All patients were informed about the study, after which they provided either written or verbal consent to participate. This study was approved by the Ethics Committee of hospital (Approval No.…”
Section: Study Populationmentioning
confidence: 99%
“…18,19 The HAMD was administered by 3 specially trained professionals through conversation and observation. Depression states were defined as follows: normal (total HAMD score of ≤ 7), possible depression (8)(9)(10)(11)(12)(13)(14)(15)(16), mild depression (17)(18)(19)(20)(21)(22)(23), and moderate to severe depression (≥ 24). The 17 items were grouped into 5 structural factors: "anxiety/somatization" (including items of psychic anxiety, somatic anxiety, GI symptoms, general somatic symptoms, hypochondriasis [self-absorption, ie, bodily, hypochondriacal delusions, etc], and insight), "mental disorders" (including items of guilt, suicide, and agitation), "retardation symptoms" (including items of depressed mood, work and interests, retardation, and genital symptoms), "sleep disturbances" (including items of initial insomnia, middle insomnia, and delayed insomnia), and "weight loss."…”
Section: Instrumental Evaluationmentioning
confidence: 99%
“…It should be noted that the magnitude of reduction in disease severity observed in our study is uncommon. Further, during the present study, the majority of patients shifted to lower IBS severity categories, some moving from a severe to a mild form of the disease, which has been associated in the literature with a decrease in health care seeking and an improvement of quality of life[ 2 , 21 ].…”
Section: Discussionmentioning
confidence: 73%